Film Production and Consumption in Contemporary Taiwan : Cinema as a Sensory Circuit - Mon, Ya-Feng (Book collections on Project MUSE., 2016)
This book uses the potent case study of contemporary Taiwanese queer romance films to address the question of how capitalism in Taiwan has privileged the film industry at the expense of the audience's freedom to choose and respond to culture on its own terms. Interweaving in-depth interviews with filmmakers, producers, marketers, and spectators, Ya-Fong Mon takes a biopolitical approach to the question, showing how the industry uses investments in technoscience, ancillary marketing, and media convergence to seduce and control the sensory experience of the audience--yet that control only extends so far: volatility remains a key component of the filmgoing experience.